Socioeconomic Risk and School Readiness: Longitudinal Mediation Through Children's Social Competence and Executive Function - Perry, Rosemarie E.; Braren, Stephen H.; Blair, Clancy; , The Family Life Project Key Investigators; Vernon-Feagans, Lynne; Cox, Martha; Blair, Clancy; Burchinal, Margaret; Garrett-Peters, Patricia; Greenberg, Mark; Mills-Koonce, Roger; Willoughby, Michael (Frontiers in Psychology, 2018)
The association of socioeconomic status with academic readiness and school achievement is well established. However, the specific contributions of cognitive and social aspects of self-regulation, and potential reciprocal relations between them in the prediction of school readiness and early school achievement have not previously been examined. This study examined mediational processes involving children's executive function (EF) skills at 58 months and Grade 1 (G1) and social competence in Kindergarten (K) and G1, as potential pathways by which early-life poverty-related risks influence Grade 2 (G2) math and reading achievement. Data came from the Family Life Project, which is a prospective longitudinal study of 1,292 children and families followed from birth in primarily low-income, non-urban counties in Pennsylvania (PA) and North Carolina (NC). Autoregressive cross-lagged mediation analyses indicated that EF at 58 months through EF at G1 mediated negative associations between cumulative risk exposure and academic skills, with this pathway mediating 36% of the total effect. Furthermore, social competence at K through EF at G1 mediated negative associations between early-life cumulative socioeconomic risk and academic skills, mediating 16% of the total effect. These findings provide evidence that poverty-related risks can influence school readiness and academic achievement via EF. Additionally, these results provide preliminary support for the premise that social competence through EF is a pathway by which cumulative poverty-related risk predicts early academic competence. Our findings are consistent with studies demonstrating developmental associations between EF and social competence. Furthermore, our findings are consistent with prekindergarten programs for children in poverty that emphasize both cognitive and social aspects of self-regulation.